Legal Basis of Cross-Border Criminal Prosecution of Cybercriminals: Criminal and Procedural Challenges for Azerbaijan - Karimov, Shohlet Muzaffar; Sharifov, Rashad Mammad; Eyvazov, Akif Maharlam (Jurnal Cita Hukum, 2025)
The impact of modern digital technologies is essential for understanding the need to improve the law enforcement system. The purpose of this article is to examine the legal basis for cross-border criminal prosecution of cybercrime in Azerbaijan, identify key criminal law and procedural challenges, and develop recommendations to improve national legislation and strengthen international cooperation. The study is based on an analysis of Azerbaijan's criminal and criminal procedure legislation in the field of cross-border prosecution of cybercrimes. Normative and comparative legal analysis methods, along with systematization, were employed to identify gaps and formulate recommendations. The results show that the Criminal Code of Azerbaijan contains references to the illegality of unauthorized access to computer information, illegal actions related to the exploitation of computer networks, and the distribution of malicious software. There is no separate article on computer fraud, so clear standards for collecting electronic evidence are not specified, indicating significant gaps in the national legal framework. The main challenges in cross-border prosecution of cybercrimes include the limited scope of bilateral extradition agreements, difficulties in cooperating with countries with different legal systems, and bureaucratic obstacles to the exchange of digital evidence. The conclusions highlight recommendations that would improve the regulatory framework. First and foremost, they point to the need to implement regulations on computer fraud and clear rules for the use of electronic evidence, expand international cooperation, and implement the provisions of international conventions to which Azerbaijan is a party.